B Corp certification in Africa: motivations, opportunities and challenges in promoting socially and environmentally responsible management practices - Grand, Savannah (Graduate School of Business (GSB), 2025)
African businesses are increasingly recognising the importance of balancing profit with social and environmental responsibility, aligning with the global trend toward sustainable practices. B Corp certification, a globally recognised standard and associated certification system, offers businesses a formal pathway to commit to these values. However, despite its international prominence, the adoption of B Corp certification in Africa remains limited. African businesses face unique challenges such as limited resources, complex regulatory environments, and varying levels of awareness about sustainability. There is limited insight into the specific motivations, challenges, and contextual factors that shape how African businesses navigate and implement the certification process. This suggests a significant gap in understanding the unique motivations, challenges, and contextual factors that influence how African businesses navigate and implement the certification process. This study contributes to addressing this gap by using purposive sampling of 12 participants and employed thematic coding to analyse qualitative data. The interviews were conducted with key stakeholders such as representatives from certified B Corps in Africa, sustainability experts and members of B Lab. The findings show that African businesses pursue B Corp certification to tackle specific social and environmental challenges while boosting their brand reputation locally and globally. The certification provides external validation that builds trust with stakeholders, including consumers, partners, and investors. It is also seen as a strategic asset for attracting socially conscious audiences and aligning business operations with international sustainability standards. The study identifies several challenges that hinder the adoption of B Corp certification in Africa. Smaller companies, in particular, find the financial burden of certification challenging. Moreover, a lack of awareness and understanding of B Corp standards, which are often not fully adapted to local contexts, further complicates the process. The study contributes to the broader discourse on sustainable business practices in Africa by offering valuable insights into how B Corp certification can drive social and environmental change on the continent